2019
DOI: 10.3390/ijerph16091494
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Fidelity, Impact and Sustainability of Participatory Workplace Health Teams in Skilled Nursing Facilities

Abstract: Organizational features of work often pose obstacles to workforce health, and a participatory change process may address those obstacles. In this research, an intervention program sought to integrate occupational safety and health (OSH) with health promotion (HP) in three skilled nursing facilities. Three facilities with pre-existing HP programs served as control sites. The intervention was evaluated after 3–4 years through focus groups, interviews, surveys, and researcher observations. We assessed process fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Additionally, personnel who work in for-profit chains may have to seek administrative approval to fill out an organizational survey, and so may be less likely to respond. 29 To address these concerns, we control for the number of federally certified beds and ownership status defined as for-profit or not-for-profit (both obtained from Medicare). To control for area characteristics that might affect the availability of the DON and other difference between rural and urban nursing homes in the United States, 30 we used the most recent (2010) Rural-Urban Commuting area codes to assign each nursing home a rurality score based on their county.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, personnel who work in for-profit chains may have to seek administrative approval to fill out an organizational survey, and so may be less likely to respond. 29 To address these concerns, we control for the number of federally certified beds and ownership status defined as for-profit or not-for-profit (both obtained from Medicare). To control for area characteristics that might affect the availability of the DON and other difference between rural and urban nursing homes in the United States, 30 we used the most recent (2010) Rural-Urban Commuting area codes to assign each nursing home a rurality score based on their county.…”
Section: Methodsmentioning
confidence: 99%
“…Larger nursing homes are likely to have more personnel, which could either positively or negatively affect the amount of time a DON has available to answer a survey. Additionally, personnel who work in for‐profit chains may have to seek administrative approval to fill out an organizational survey, and so may be less likely to respond 29 . To address these concerns, we control for the number of federally certified beds and ownership status defined as for‐profit or not‐for‐profit (both obtained from Medicare).…”
Section: Methodsmentioning
confidence: 99%
“…TWH intervention research has retrospectively identified facilitators to program implementation such as perceived program feasibility (Farewell et al, 2020), employee engagement and building dedicated roles such as on-site champions (Zhang et al, 2016). Similarly, retrospective evaluations reported barriers to participatory TWH interventions, including staffing issues (Farewell et al, 2020), difficulty to secure time for intervention activities, lack of communication, hierarchical decision-making structures (Zhang et al, 2016) and the ongoing challenge of sustaining program support in the face of leadership changes and normal turnover (Kotejoshyer et al, 2019;Strickland et al, 2019). While there could also be obstacles on the part of employees, these obstacles primarily point to management practices and reluctance to commit to recruitment, uptake and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…TWH intervention research has retrospectively identi ed facilitators to program implementation such as perceived program feasibility (25), employee engagement (25,26), and building dedicated roles such as on-site champions (26). Similarly, retrospective evaluations reported barriers to participatory TWH interventions including sta ng issues (25), di culty to secure time for intervention activities (26), lack of communication (26), hierarchical decision-making structure (26), and struggle to sustain leadership support (27,28). However, it is unclear how readily these obstacles could be observed prior to engaging the workplaces in the intervention process.…”
Section: Introductionmentioning
confidence: 99%